AD-DAKHIL DALAM TAFSIR KEPEMIMPINAN ISLAM: ANALISIS SURAH AL-MAIDAH AYAT 55 DALAM TAFSIR AL-MIZAN KARYA AT-THABATHABA’I - Milla Nur Syafa'ati (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Leadership in Islam is a crucial concept that intertwines theological and social dimensions. Surah Al-Māidah verse 55 is often cited in leadership discourse, particularly by Shia scholars who interpret the verse as divine legitimation of the Imamate of Ali ibn Abi Talib. This study aims to analyze the interpretation of the verse in Tafsir al-Mīzān by Allamah Thabathaba’i and identify elements of ad-dakhil—foreign or unauthorized insertions—within the interpretation that may affect its objectivity. This research employs a qualitative descriptive method with a thematic and literature-based approach. The findings show that Thabathaba’i interprets the verse through a Shia theological framework, referencing the narration of Ali donating a ring while in rukū' (bowing in prayer). However, several narrations used as supporting evidence are considered weak in terms of transmission and content by various hadith scholars, thus falling under the category of ad-dakhil. This study concludes that the interpretation of leadership-related verses requires careful methodological scrutiny to avoid distortions in meaning caused by unauthenticated sources. Keyword: Ad-Dakhil, Tafsir Al-Mizan, Surah Al-Maidah:55, Islamic Leadership, Imamah.